Impacts of climate change on streamflow and floodplain inundation in a coastal subtropical catchment. (January 2021) - Eccles, Rohan; Zhang, Hong; Hamilton, David; Trancoso, Ralph; Syktus, Jozef
Highlights: Effects of climate change and sea level rise on flows and floods were assessed. High and mean flows decreased substantially in winter and spring. Large variability in the projections of major flood events. Larger flood events tended towards an increase and smaller events did not change. Sea level rise significantly increased floodplain inundation by the 2050s and 2080s. Abstract: Climate change is expected to significantly alter river hydrological regimes throughout the world, affecting water resources and the frequency of floods and droughts. The objectives of this study were to determine the impacts of climate change and sea level rise on streamflow and floodplain inundation in the subtropical Logan-Albert catchment, Australia. An ensemble of 11 high-resolution climate models forced under high (Representative Concentration Pathway 8.5 - RCP8.5) and intermediate-emission (RCP4.5) scenarios was applied. There was considerable variation from the model ensemble result in projections of major flooding events at 5 and 100-year average recurrence intervals (ARIs). The largest events (100-year ARI) tended towards an increase, whereas the smallest (5-year ARI) tended towards a decrease. Floodplain inundation from a 100-year ARI event increased in all simulations and inclusion of sea level rise resulted in increased floodplain inundation area nearly doubling by the end of the century, which has substantial implications for flood risk. Our study highlights the non-linear nature of climate change impacts on streamflow and floodplain inundation, demonstrating the need for a comprehensive assessment at the floodplain scale when informing preparedness for future flooding events.